Post-starburst galaxies in different environments. Issue Volume 15:Issue S359(2020) (March 2019) - Spindler, Rodolfo; Trevisan, Marina; Schnorr-Müller, Allan
Abstract: Post-starburst galaxies (PSBGs) are systems that experienced a burst followed by a rapid quenching of star formation. However, it is still unclear what causes these events and what is the environmental role in the origin of PSBGs. To address this, we analysed sizes, morphologies, ages, and metallicities of PSBGs at 0.05 ≤ z ≤ 0.1 in groups and clusters of galaxies. We find a statistically significant excess of compact PSBGs in groups compared to a control sample of passive galaxies. Satellite PSBGs in groups tend to be more compact compared to their counterparts in clusters. Additionally, the PSBGs in groups have smaller T-type values and are likely to be found in inner group regions compared to PSBGs in clusters. Our results are compatible with dissipative wet merger events being an important mechanism responsible for the origin of PSBGs in groups, but other – less dissipative – processes may be producing PSBGs in cluster environments.